Tissue Engineering: A Modular Strategy to Engineer Complex Tissues and Organs (Adv. Sci. 5/2018). Issue 5 (May 2018) - Dikina, Anna D.; Alt, Daniel S.; Herberg, Samuel; McMillan, Alexandra; Strobel, Hannah A.; Zheng, Zijie; Cao, Meng; Lai, Bradley P.; Jeon, Oju; Petsinger, Victoria Ivy; Cotton, Calvin U.; Rolle, Marsha W.; et al.
Abstract : In article number1700402, Eben Alsberg and co‐workers report the engineering of tri‐tissue tracheas using a scaffold‐free approach that allows for the integration of structural cartilage rings, prevascular blood vessel networks, and epithelial cells into a single construct. Neotracheas of various dimensions, including human size, are formed via cellular self‐assembly. Prevascular tracheas are subcutaneously implanted into mice and demonstrate anastamosis with and perfusion by host vasculature.